Predictive and prognostic significance of placental growth factor in pregnant women at high-risk for development of preeclampsia - Meena, Jyoti; Dhiman, Soniya; Singh, Archana; Vanamail, Perumal; Singhal, Seema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The study aimed to assess the predictive and prognostic role of placental growth factor (PlGF) in high-risk antenatal women for development of preeclampsia (PE). Methods: In this observational cohort study, antenatal women with gestation age from 20 to 32 weeks with high risk for development of PE were included. Serum PlGF was estimated by sandwich ELISA technique. A p-value of less than .05 was considered significant. Results: A total of 286 high-risk women were analysed for development of PE and obstetric outcomes. Of these 97/286 (34%) developed PE and 62/286 (21.7%) had abnormal PlGF value ( 100 pg/ml). Among the women with abnormal PIGF, 48 (77.4%) developed PE and out of 224 women with normal PIGF level, 49 (21.9%) developed PE resulting in a significant (p<0.001) odds ratio of 12.2 (95% CI: 6.0-25.9). For prediction of PE, a sensitivity and specificity of more than 75% at a cut-off value of <204.5 pg/ml was observed by ROC curve analysis. For prediction of preterm delivery (<34 weeks), a sensitivity and specificity of 65% was observed at a cut-off value of PlGF 191.7 pg/ml. Obstetric complications like eclampsia, preterm births (<34 weeks), neonate with low 5-minute APGAR score, low birth weight, fetal growth restriction, still-births and neonatal intensive care unit admissions all were significantly higher in abnormal PlGF group compared with normal PlGF group (p<0.05). Conclusions: Serum PlGF levels can provide valuable information for the prediction of PE and preterm births and abnormal PlGF values showed a significant association with adverse obstetrical outcomes.